Modulation of mammalian translation by a ribosome-associated tRNA half - Gonskikh, Yulia; Koš, Martin (RNA biology, 2020)
Originally considered futile degradation products, tRNA-derived RNA fragments (tdRs) have been shown over the recent past to be crucial players in orchestrating various cellular functions. Unlike other small non-coding RNA (ncRNA) classes, tdRs possess a multifaceted functional repertoire ranging from regulating transcription, apoptosis, RNA interference, ribosome biogenesis to controlling translation efficiency. A subset of the latter tdRs has been shown to directly target the ribosome, the central molecular machine of protein biosynthesis. Here we describe the function of the mammalian tRNAPro 5ʹ half, a 35 residue long ncRNA associated with ribosomes and polysomes in several mammalian cell lines. Addition of tRNAPro halves to mammalian in vitro translation systems results in global translation inhibition and concomitantly causes the upregulation of a specific low molecular weight translational product. This tRNAPro 5ʹ half-dependent translation product consists of both RNA and amino acids. Transfection of the tRNAPro half into HeLa cells leads to the formation of the same product in vivo. The migration of this product in acidic gels, the insensitivity to copper sulphate treatment, the resistance to 3ʹ polyadenylation, and the association with 80S monosomes indicate that the accumulated product is peptidyl-tRNA. Our data thus suggest that binding of the tRNAPro 5ʹ half to the ribosome leads to ribosome stalling and to the formation of peptidyl-tRNA. Our findings revealed a so far unknown functional role of a tdR thus further enlarging the functional heterogeneity of this emerging class of ribo-regulators.
Gesehen am 26.11.2021